A proposed framework for best practice in Quality Assurance in Namibian Higher education institutions (Journal for Studies in Humanities and Social Sciences, 2015)
This study investigated into the current status of quality assurance in the relatively young higher education sector of Namibia, where the official quality assurance system still is in the process of development. The purpose of the study was to determine the status and level of quality assurance mechanisms within Namibian higher education institutions with reference to current international quality assurance practices. The study confined itself to degree-granting higher education institutions only, with a university status. Three institutions participated in the study - one public university, one private university, and one polytechnic. A phenomenological explorative and descriptive design was used with the aim of seeking an understanding and interpretation of the true meaning that the participants accorded to their experience of the phenomenon under study, namely, quality assurance in higher education institutions. The methodology was based on improvement-oriented evaluation. The data were collected by means of individual interviews (purposeful sampling) and institutional document analyses.